Optimal Prognostication of Patients with Coronary Stenoses in the Pre- and Post-PCI setting: Comments on TARGET FFR and DEFINE-FLOW Trials Presented at TCT Connect 2020 - Andreas Seitz; Stefan Baumann; Udo Sechtem; Peter Ong (European Cardiology Review)
The body of evidence for the use of coronary physiology assessments to guide percutaneous coronary intervention (PCI) has been growing continuously in recent decades. Two studies presented during TCT Connect 2020 added insights into the prognostic value of coronary physiology measurements in pre- and post-PCI settings. The first study, TARGET FFR, assessed whether a post-PCI fractional flow reserve (FFR)-guided incremental optimisation strategy (PIOS) was superior to angiography-guided PCI. The second study, DEFINE-FLOW, assessed the course of stenoses with fractional and coronary flow reserve (FFR+/CFR−) discordance when treated medically. This article summarises the main results from the TARGET FFR and the DEFINE-FLOW trials and puts them into the context of the existing literature.